2023
DOI: 10.3390/su15107912
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Restorative Potential of Urban Parks by Citizens—A Case Study from Wrocław, Poland

Aleksandra Szkopiecka,
Joanna Patrycja Wyrwa,
Grzegorz Chrobak
et al.

Abstract: Providing restorative green areas is important, especially in the city, where the level of stress and noise is relatively high. Therefore, green areas, such as urban parks, should provide coherent audio–visual stimuli to achieve positive perception by the residents. Therefore, this study aims to investigate the potential for psychological regeneration in urban parks in terms of visual and soundscape assessment as well as to assess the role of the intensity of different types of sound contributing to the positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The sound environment, particularly when it features natural sounds like bird songs, wind rustling through trees, and water, can enhance the visual landscape's appreciation, whether composed of various types of vegetation or undulating terrain [96]. Some researchers suggest that visual stimuli are more important than auditory ones in environmental perception, though they acknowledge that soundscape quality is crucial for enhancing the restorative potential of urban green areas [122]. When analyzing visibility, it is common to focus solely on the visibility of greenery.…”
Section: Impact Of Sound On the Features Of Green Spacesmentioning
confidence: 99%
“…The sound environment, particularly when it features natural sounds like bird songs, wind rustling through trees, and water, can enhance the visual landscape's appreciation, whether composed of various types of vegetation or undulating terrain [96]. Some researchers suggest that visual stimuli are more important than auditory ones in environmental perception, though they acknowledge that soundscape quality is crucial for enhancing the restorative potential of urban green areas [122]. When analyzing visibility, it is common to focus solely on the visibility of greenery.…”
Section: Impact Of Sound On the Features Of Green Spacesmentioning
confidence: 99%
“…From the perspective of research area, most of the soundscape restorative research now is in public spaces such as urban parks, forest parks, college campuses, etc., and there are fewer researches involving rural tourist destinations. In addition, scholars have already confirmed that soundscape has restorative functions [72][73][74], but there is a lack of research on its influence mechanism with environmental restorative effects. Therefore, in this study, the Taohuayuan Scenic Area in Changde City, Hunan Province was selected as a case study for empirical analysis, with the main purpose of exploring the influence mechanism of Rural Soundscape Perception on Environmental Restoration Perception by constructing a structural equation model, and introducing the two affective variables of tourism nostalgia and place attachment, to provide new research perspectives for the theoretical study of Rural Soundscape Perception, and at the same time, to provide theoretical basis for the design and creation of soundscape in rural tourism destinations and decision-making support.…”
Section: Introductionmentioning
confidence: 99%
“…Because most older adults prefer to stay at home [6], the role of urban parks near where older adults live is particularly important. Firstly, they provide older residents with access to the natural environment, which helps older adults gain positive physical and mental benefits [7][8][9][10][11]. Secondly, urban parks provide spatial places for doing physical activities.…”
Section: Introductionmentioning
confidence: 99%